Dual sourcing as a risk mitigating option - A study at Volvo Group Trucks purchasing - Bertilsson, Johan; Franzén, Gustav (My University, 2015)
Owing to last decades' globalization and increased customer demands, outsourcing has increased, causing companies to spend more money on external suppliers, making purchasing a strategic issue for most companies. Mitigating the increased supply risk that follows from this has become an important topic and one way of doing this is by adopting dual sourcing. This often comes with increased costs and the difficulty lies in knowing the benefit received for the cost spent. This thesis is carried out as a case study at Volvo Group Trucks. Today single sourcing is the general rule at Volvo but when disturbance situations arise causing financial impacts on Volvo, the concept of dual sourcing as a risk mitigating option is raised. The purpose of this thesis has therefore been to investigate dual sourcing of components as a way to mitigate risk and through this, enhance the supplier risk management process at Volvo. To fulfill the purpose, 36 interviews with employees within different departments at Volvo have been held as well as 4 interviews with purchasing representatives from external companies. Also, case studies of suppliers causing disturbance to Volvo have been conducted with the purpose of comparing the total costs arising from the disturbance situation with the costs of the hypothetical situation of having a dual source in place during the disturbance. The main conclusion of this thesis is that dual sourcing should not primarily be used to mitigate risk due to the associated costs with it. Instead, component criteria consisting of commonality and resourcing time was found which could be used as a screening criteria that together with other factors on a case-by-case basis decide whether dual sourcing should be evaluated as a risk mitigating option or not. From the criteria, an assessment of a component’s business interruption value can be done, which is a quantitative estimation of the financial consequences of an incoming component’s disruption.
Keywords: Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics; Transport